2023
DOI: 10.1039/d2bm01543a
|View full text |Cite
|
Sign up to set email alerts
|

Nano-encapsulation of halofuginone hydrobromide enhances anticoccidial activity against Eimeria tenella in chickens

Abstract: HF-loaded TPGS polymer micelles (HTPM) were developed to improve the anticoccidial effect of loaded drugs by enhancing cellular take up, denaturing merozoites inside infected cells, and restoring the gut microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The samples (Lar API, blank Fe-MOF carrier, a Lar and Fe-MOF physical mixture, and Lar@Fe-MOF) and an appropriate amount of Frontiers in Bioengineering and Biotechnology frontiersin.org potassium bromide were mixed in proportion and pressed into tablets. The tablets were then scanned by an FTIR spectroscopy instrument with a wavenumber range of 4,000-400 cm -1 and a resolution of 4 cm -1 (Lin et al, 2023).…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysismentioning
confidence: 99%
“…The samples (Lar API, blank Fe-MOF carrier, a Lar and Fe-MOF physical mixture, and Lar@Fe-MOF) and an appropriate amount of Frontiers in Bioengineering and Biotechnology frontiersin.org potassium bromide were mixed in proportion and pressed into tablets. The tablets were then scanned by an FTIR spectroscopy instrument with a wavenumber range of 4,000-400 cm -1 and a resolution of 4 cm -1 (Lin et al, 2023).…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysismentioning
confidence: 99%
“…Kasem et al in another study evaluated the in vitro anticoccidial activities of an ultrasonicated ethanolic extract of Rosmarinus officinalis (UEERO) and its chitosan-based nanoparticles (UEERO-Cs NPs) on Eimeria tenella oocysts of chickens . Also, Lin et al in their findings indicated that the anticoccidial efficacy of Halofuginone hydrobromide (HF) was significantly enhanced after being encapsulated in polymer micelles and further demonstrated the potential protective application of nanoencapsulating anticoccidial drugs as a promising approach to control coccidiosis in poultry . Moreover, Zhang et al prepared MAD-loaded nanostructured lipid carriers (MAD–NLCs) to overcome the defects of Maduramicin ammonium (MAD) by using highly soluble nanostructured lipid carriers (NLCs).…”
Section: Introductionmentioning
confidence: 99%
“…16 Also, Lin et al in their findings indicated that the anticoccidial efficacy of Halofuginone hydrobromide (HF) was significantly enhanced after being encapsulated in polymer micelles and further demonstrated the potential protective application of nanoencapsulating anticoccidial drugs as a promising approach to control coccidiosis in poultry. 17 Moreover, Zhang et al prepared MAD-loaded nanostructured lipid carriers (MAD−NLCs) to overcome the defects of Maduramicin ammonium (MAD) by using highly soluble nanostructured lipid carriers (NLCs). In their investigation, the formulation was optimized via a three-level, three-factor Box−Behnken response surface method.…”
Section: Introductionmentioning
confidence: 99%